Wind energy in Serbia: Harmonization with the legislation of the European Union. Issue 9 (3rd October 2018) - Ljubojev, Nadezda; Pekez, Jasmina; Radovanovic, Ljiljana
ABSTRACT: Promoting innovative renewable sources and reinforcing the wind energy market will contribute to preservation of the ecosystem by reducing emissions at global and local levels. The topic of the present paper is the analysis of the legal framework required for wind energy use in the Republic of Serbia. The paper discusses the harmonization of the domestic legislation with the global and European trends in this area as well as the obligations undertaken under international documents ratified within the European integration process. Wind energy use in the Republic of Serbia is far below the level which the country is expected to reach as one of the obligations under the Energy Community Treaty. The proposed measures that should be taken to increase the use of wind energy resources in the Republic of Serbia are legal and administrative measures, financial and investment measures, technology development, capacity building, human resources and infrastructure, awareness raising and education.